2020
DOI: 10.3389/fpsyg.2020.00430
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Parenting Intentions Among Childfree Gay Men: A Comparison With Lesbian Women and Heterosexual Men and Women

Abstract: Introduction: There is a growing interest in the parenting intentions of gay men. Prior research has found that gay men are less likely to become parents compared to their heterosexual and lesbian peers, but we know very little about why this discrepancy exists. Our first aim was to investigate whether the strength of parenting intentions is similar or different among childfree gay men compared to lesbian women, and heterosexual men and women. Our second aim was to explore the extent to which the theory of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Nowadays, more LGBTQ individuals are becoming parents than ever before due to changes in legislation and advances in fertility technologies [ 39 , 40 ]. Consequently, research on parenthood aspirations in this population has been growing worldwide, e.g., [ 41 , 42 , 43 , 44 , 45 ], including in Israel, e.g., [ 38 , 46 ]. Previous studies have suggested that there are three main common factors that define whether an individual will actually become a parent in the future: parenthood desire (i.e., expressed wishes); parenthood intention (i.e., explicit reflecting/planning to become a parent); and estimated likelihood of parenthood (i.e., assessing the probabilities of becoming a parent, which also takes into account the sociocultural conditions) [ 38 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, more LGBTQ individuals are becoming parents than ever before due to changes in legislation and advances in fertility technologies [ 39 , 40 ]. Consequently, research on parenthood aspirations in this population has been growing worldwide, e.g., [ 41 , 42 , 43 , 44 , 45 ], including in Israel, e.g., [ 38 , 46 ]. Previous studies have suggested that there are three main common factors that define whether an individual will actually become a parent in the future: parenthood desire (i.e., expressed wishes); parenthood intention (i.e., explicit reflecting/planning to become a parent); and estimated likelihood of parenthood (i.e., assessing the probabilities of becoming a parent, which also takes into account the sociocultural conditions) [ 38 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…We included heterosexual Brazilians of both genders and over the age of 18. The exclusion of non-heterosexual individuals is due to the fact that studies on CM carried out with these groups (Blake et al, 2017;van Houten, Tornello, Hoffenaar, & Bos, 2020) indicate the need to include and problematize a set of individual and contextual variables, which address concerns unique to their sexual minority status, that were not considered in this study. Data was collected virtually via the online platform Surveymonkey, between December 2018 and July 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Their childlessness does not relate to an absence of parental consciousness. Just as childless gay men who lack parental consciousness and see their childlessness as "naturally" given, childfree gay men consider their childlessness as a permanent way of life; but as opposed to the former, they construct this way as their genuine choice (e.g., van Houten et al, 2020).…”
Section: Childlessness As a Choicementioning
confidence: 99%